2017
DOI: 10.1089/mdr.2015.0311
|View full text |Cite
|
Sign up to set email alerts
|

A Snapshot of Co-Resistance to Carbapenems and Tigecycline in Clinical Isolates ofEnterobacter cloacae

Abstract: Enterobacter cloacae is one of the most common carbapenem-resistant Enterobacteriaceae (CRE) global wide. Resistance to tigecycline, one of the few therapeutic options for CRE infections, in carbapenem-resistant E. cloacae is of clinical significance. Fourteen E. cloacae clinical isolates (EC1-EC14) co-resistant to tigecycline and carbapenems were studied. Two tigecycline-susceptible/carbapenem-resistant isolates (TS1-TS2) were used for comparison. Genotyping by pulsed-field gel electrophoresis and multilocus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Although previous studies reported the additive role of ESBL production, decreased OMP expression and an active efflux pump system towards carbapenem resistance development, association of carbapenemases with OMP loss and acrB upregulation was not explored before262728. In addition to exploring the well-known association between ESBL production and acrB upregulation/porin loss, a significant association of carbapenemase production with acrB upregulation was observed in the current study among CREs.…”
Section: Discussionmentioning
confidence: 67%
“…Although previous studies reported the additive role of ESBL production, decreased OMP expression and an active efflux pump system towards carbapenem resistance development, association of carbapenemases with OMP loss and acrB upregulation was not explored before262728. In addition to exploring the well-known association between ESBL production and acrB upregulation/porin loss, a significant association of carbapenemase production with acrB upregulation was observed in the current study among CREs.…”
Section: Discussionmentioning
confidence: 67%
“…Treatment problems were mainly found in the treatment of CRE infection with only a few antimicrobial options, including polymyxin, aminoglycosides, tigecycline and fosfomycin [ 25 , 26 ]. In the possible combination regimen, the effect of carbapenem treatment remains to be determined, such as high-dose infusion or double carbapenem treatment [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this pathogen has also been reported to contaminate medical equipment in hospitals (Davin-Regli and Pagès, 2015). Clinical isolates of E. cloacae were previously reported to be resistant against carbapenem, tigecycline, colistin (Huang et al, 2017). It was found that out of 385 patient specimens, 64.68% were found to be positive for pathogenic bacteria, including E. cloacae (2%).…”
Section: Introductionmentioning
confidence: 99%